An environmental sustainability roadmap for partially substituting agricultural waste for sand in cement blocks - Mohammed, Sazid Ali; Shakor, Pshtiwan; S., Sathvik; Rauniyar, Abishek; Krishnaraj, L.; Kumar Singh, Atul; Laghi, Vittoria (Frontiers in Built Environment, 2023)
Agricultural waste can be used in cement block production for a number of reasons, including its environmental, economic, and labor benefits. This study examines the mechanical, durability, and cost-effectiveness characteristics of cement blocks. A cement block made from agriculture waste promotes sustainable construction practices, since waste agriculture is often dumped in landfills and regarded as a waste material. Carbon dioxide (CO2) emissions produced by the construction sector, either from the firing of clay bricks or from the production of cement, contribute significantly to global warming. In many developing countries, air pollution from agricultural activities is primarily accounted for the emissions from agricultural machinery and openly burning agro-waste. Farming is one of the leading causes of water and soil pollution.Hence, adopting agricultural waste into cement production would significantly reduce the environmental impact of concrete structures. The goal of this research is to determine whether agricultural waste products, such as vermiculite, pistachio shells, sugarcane bagasse, and coconut husks, can be used to substitute sand in concrete blocks. The water absorption capacity of waste materials, density, flexural strength, fire resistance, and compressive strength of waste 2 materials as admixtures in concrete were evaluated using experimental tests. In most cases, the concrete blocks made from agricultural waste were strong enough to satisfy ASTM standards.The specimens containing coconut husks and pistachio shells, among others, were found to be fairly strong and durable, even when isolating them from water.